Local cultural identity representation at the Yogyakarta International Airport gate - Rr. Chandrarezky Permatasari; SM. Wardhana; YN. Utomo (Pascasarjana Institut Seni Indonesia Surakarta, 2023)
Airports serve as a gateway for tourists as well as an introduction to local cultural opportunities, connecting regions, provinces, and countries. The application of local cultural aesthetic elements in airport public spaces is necessary due to conditions where the heavy influence of globalization can threaten the sustainability and the existence of local wisdom identity. This research aims to identify the potential of Javanese and Yogyakarta Cretan cultural elements, forming architectural designs and decorative elements at Yogyakarta International Airport's gates by the interior entrance access and the values contained therein. This research method uses qualitative methods with the ATUMICS theory approach to analyzing traditional elements (past culture) that can be integrated with modern features (present) in interpreting the existence of a form of local cultural identity. The results of this study suggest that the existence of local culture in the gapura and entrance gate in depicting micro symbols plays a significant influence. The Jogja palace feels present as it creates a feeling of place for its presence at Yogyakarta International Airport. The findings demonstrate that the object of research has an essential function in developing local identity as a symbol of archipelago architecture and as a possible magnet for introducing local culture so that it can be preserved by modernization.